How transformative innovations shaped the rise of nations : from ancient Rome to modern America - Tellis, Gerard J., 1950-; Rosenzweig, Stav (London : Anthem Press, 2018)
Over the last 2,000 years, critical innovations have transformed small regions into global powers. But these powers have faded when they did not embrace the next big innovation. Gerard J. Tellis and Stav Rosenzweig argue that openness to new ideas and people, empowerment of individuals and competition are key drivers in the development and adoption of transformative innovations. These innovations, in turn, fuel economic growth, national dominance and global leadership. In How Transformative Innovations Shaped the Rise of Nations, Tellis and Rosenzweig examine the transformative qualities of concrete in Rome; swift equine warfare in Mongolia; critical navigational innovations in the golden ages of Chinese, Venetian, Portuguese and Dutch empires; the patent system and steam engine in Britain; and mass production in the United States of America.
Global influence of transformative innovation -- Roman concrete: foundations of an empire -- Swift equine warfare and the rise of Mongol power -- How gunpowder shaped the fortunes of nations -- Golden age of Chinese water navigation -- Venetian shipbuilding: mastering the Mediterranean -- Portuguese caravel: building an oceanic empire -- Fluyt and the building of the Dutch empire -- Patenting: institutionalizing innovation -- The steam engine and the rise of British empire -- American mass production and the rise of the United States.
Title from publisher's bibliographic system (viewed on 05 Jul 2018).
Keywords: Technology and civilization